Can the appellant’s non-attendance at the oral hearing generate effects on the Labour Process under Act no. 29497? - Rodríguez Riojas, Juan Ismael (2020)
The principle of orality has become one of the main foundations of labour process according to the Peruvian New Labour Process Act No 29497. Also, in harmony with the other principles, it guarantees celerity and efficiency in the current labor procedural model. In that sense, the use of oral hearing, even at the appeal stage, with the duty of oral support of the appeal remedy, does not impose a disproportionate or unreasonable burden. Following this order of ideas, the objective of this article is to illustrate to the legal community the effects to be generated by nonattendance, and to analyse whether the application of these effects implies an «inequality of arms» in the labour judicial process.